Libraries, information and resource centres as a tool for women and economic development in Nigeria (2004)
The role of women libraries, documentation and resource centres in the economic development of women is examined and the types of literature gathered, processed and disseminated is surveyed. The actvities of the centres concerning women education, information literacy level and the economic activities of the women in the community were observed and assessed to find out the impact they have on society. Women Special Centres and NGOs were used in the study. Questionnaire, interview and participatory observation methods were used in data gathering. The results show that the Women centers run literacy programs for women and girls and also provide training for less priviledged women to facilitate their economic independence as they make a living from skills acquired through vocational training. Women farmers are assisted in getting loans, and the libraries provide needed literature in book and audio-visual form for them. Information related to their reproductive health is also provided. Women depend to a great extent on the resources and facilities of these centres. Recommendations are made on how Information and Communication Technologies (ICTs) can be used to greater advantage to network and reach majority of women especially in the rural community.